High precision electrolytic polishing of ni–ti shape memory alloy for biomedical vascular stents - Han, Deokhyun; Yang, Hyunseok; Kong, Man Sik; Lee, Changhee; Sharma, Ashutosh; Ahn, Byungmin (Materials Express, 2020)
There is a continuous demand for multi-disciplinary design approaches for the development of new implant materials. A potential biomaterial that is suitable for vascular stents and catheters is Ni–Ti alloy (Nitinol), which exhibits excellent biocompatibility, superelasticity, and shape memory effects. Corrosion resistance of Ni–Ti vascular stents in body fluids is significantly dependent on its surface finishing characteristics. In the study, as-drawn Ni–Ti wires were electropolished from a methanolic sulfuric acid electrolyte. The effect of various electropolishing (EP) parameters, i.e., current density, electropolishing time, and electrode gap, on the surface properties of Ni–Ti wires were examined. The surface morphology and topography of the Ni–Ti wires were characterized via scanning electron microscopy (SEM) and atomic force microscopy (AFM). The root mean square (Ra) surface roughness of electropolished Ni–Ti wires was also measured using AFM. The results indicated that the surface finishing of Ni–Ti alloy exhibited maximum sensitivity to electropolishing current density. An optimum combination of surface morphology and roughness was obtained at a parameter set with current density of approximately 0.5 A/cm2, polishing time of 10 s, and electrode gap of 1.0 cm.
Keywords: Atomic Force Microscopy; Electropolishing; Nitinol; Shape Memory Alloy; Surface Roughness